RESPONSIBILITIES OF DEED LAND BUILDERS OFFICERS (PPAT) BUY SELL IN MAKING DEED LAND DISPUTE (Analysis of Supreme Court Decision No. 826 K / Pdt / 2018) - Mugiyatno Mugiyatno; Diyono Diyono; Akhmad Khisni (Program Magister (S2) Kenotariatan, Fakultas Hukum, Universitas Islam Sultan Agung, 2020)
The purpose of this study was to analyze 1) Liability Land Deed Official (PPAT) in the manufacture of the deed of sale of land. 2) .Menganalisis the validity of the deed of sale made by PPAT.3). Analyzing the legal consequences Supreme Court Decision No. 826 K / Pdt / 2018 against the Land Deed Official (PPAT) who manufacture a deed of sale of land disputes.The approach method in this research is the empirical jurisdiction. Specifications of this research is descriptive analysis. The source of the data used is primary and secondary data. The primary source is the Supreme Court decision number 826K / Pdt / 2018, while secondary data sources are taken from books and other related iteratorr, obtained through interviews and literature, while data analysis is a descriptive analytic. The method of data collection is the engineering library (library research).Results of the research results can be concluded: 1) Obligation PPAT is a deed as evidence has implemented a legal act of buying and selling, and registered under the name of the office to Pertanahan.2) Validity of PPAT Deed governed and determined by the current Minister of National Land Agency, it is affirmed in Article 21 paragraph (1) of Government Regulation No. 37 of 1998 which states that the PPAT deed made in the prescribed form of the National Land Agency. 3). The legal consequences Supreme Court Decision No. 826 K / Pdt / 2018 is the Deed of Sale and Purchase of Land Disputes number 186/2015 and certificate of land with 1394 numbers became invalid / void and not legally binding and PPAT and Land Agency may be penalized for committed an unlawful act.Keywords : offense, purchase agreement, land deed official